Phytochemical profiling of bioactive compounds, anti-inflammatory and analgesic potentials of Habenaria digitata Lindl.: Molecular docking based synergistic effect of the identified compounds. (12th June 2021) - Mahnashi, Mater H.; Alyami, Bandar A.; Alqahtani, Yahya S.; Jan, Muhammad Saeed; Rashid, Umer; Sadiq, Abdul; Alqarni, Ali O.
Abstract: Ethnopharmacological relevance: Members of Orchidaceae family has a long history in herbal and Chinese medicines. Members of this family are most commonly famous in the management of inflammation and analgesia in folk medicine. Habenaria digitata, an unexplored specie of Orchidaceae is found in North areas of Pakistan and is used by the local population for the management of analgesia and inflammation. Aim of the study: Based on the effective outcomes of the natural products as alternative therapies, we have evaluated Habenaria digitata for the management of analgesia and inflammation. The aim of the designed project is to provide a scientific basis of using this plant for the management of analgesia and inflammation. Materials and methods: The H. digitata crude extract (Hd.Cr) and subfractions, i.e. n -hexane (Hd.Hex), chloroform (Hd.Chf), ethyl acetate (Hd.EtAc), n-butanol (Hd.Bt) and aqueous (Hd.Aq) were used. The GC-MS analysis was used for the identification of phytochemicals. The plants samples were subjected to cyclooxygenase (COX 2) and lipoxygenase (5-LOX) enzymes assays. The hot plate model, acetic acid induced writhing and formalin induced paw licking models were used for in-vivo analgesic studies. The in-vivo anti-inflammatory potential was determined with carrageenan induced paw edema test. Molecular docking studies of the identified compounds were carried out by using Molecular Operating Environment (MOE, 2016.08). Results: The GC-MS analysis confirmed sixty-five compounds in Hd.Cr. Among the fractions, Hd.Chf and Hd.EtAc displayed highest activities. The observed IC50 values were 21.30 and 32.39 μg/ml against COX 2 while 14.42and 16.40 μg/ml for 5-LOX respectively. The in-vivo inflammatory and analgesic studies were pre-requisited with acute toxicity tests. In carrageenan induced inflammation, Hd.Chf excelled the standard drug aspirin by giving 62.92% inhibition of paw edema at 4 th h. Similarly, at highest concentration (75 mg/kg) of acetic acid induced analgesia, Hd.Chf was more potent than the standard drug. In formalin method, Hd.Chf exhibited 85.81% inhibition at phase-I and 74.15% at Phase-II. In hot plate model, Hd.Chf exhibited average reaction time of 10.90 at 15, 30, 45 and 60 min intervals. Docking studies supported our results and confirm the synergistic effects of phytochemicals. Conclusions: Our experimental results concluded that H. digitata contains several bioactive compounds. These bioactive compounds synergistically have therapeutic efficacy for the management of inflammation and analgesia. We have confirmed both of these potentials from the in-vitro and in-vivo experiments. Moreover, it is also obvious that the chloroform and ethyl acetate fractions are rich in these bioactive compounds. Specifically, the Hd.Chf is observed to be more practical in all the tested models of analgesia and inflammation. Computed binding energies of the compounds revealed that all the compounds have synergistic effect to prevent analgesia and inflammation. Graphical abstract: Image 1 Highlights: Identifications of bioactive compounds via GC-MS in Habenaria digitata. The in-vitro assays using cyclo and lipoxygenase assays. In-vivo anti-inflammatory assay using experimental animals. In-vivo analgesic models using experimental animals. Molecular docking studies of the identified compounds.